Persepsi Mahasiswa IAIN Pontianak terhadap Mata Kuliah Bahasa Mandarin - Sri Maulidiana (Departement of Mathematics Education, 2023)
This qualitative research study aims to explore the perceptions of IAIN Pontianak students towards Mandarin courses. The study utilized questionnaires and field observations to collect data from 100 respondents who were students from three different study programs. The results of the study indicate that most students perceive Mandarin language courses positively, and this is reflected in their good grades. The study's findings suggest that Mandarin courses are well-received among IAIN Pontianak students, which could indicate an increased interest in learning the language. Moreover, the research can also help identify areas of improvement for Mandarin language courses in the future. The use of questionnaires and field observations as data collection techniques enhances the study's validity and reliability, as it provides a more comprehensive understanding of the students' perceptions. In conclusion, this study contributes to the existing body of knowledge on language education in Indonesia, particularly in IAIN Pontianak. It highlights the importance of language courses and how students perceive them. Furthermore, this study can serve as a reference for educators to improve Mandarin language courses to meet students' needs and expectations.